Coupling Implicit Monte Carlo Thermal Radiation Transport to Lagrange and ALE Hydrodynamics in the Lab and Fluid Frames. Issue 3 (15th April 2016) - Gentile, N. A.
ABSTRACT: The requirements for coupling an Implicit Monte Carlo thermal radiation transport package to a hydrodynamics package are discussed. The calculation of material motion corrections for the radiation package in both lab and fluid frames are considered, as are the consequences of operator splitting on discretization error. We demonstrate accurate radiation hydrodynamics simulations of a radiating shock problem with both Lagrangian and Arbitrary Lagrange–Eulerian (ALE) hydrodynamics in both the lab and fluid frames.